Radiographic diagnosis of dental restoration misfit: a systematic review. (21st August 2014) - Liedke, G. S.; Spin‐Neto, R.; da Silveira, H. E. D.; Wenzel, A.
Summary The objective of this study was to perform a systematic review on the use of radiographic methods for the diagnosis of misfit in dental prostheses and restorations. The MEDLINE bibliographic database was searched from 1950 to February 2014 for reports on the radiographic diagnosis of misfits. The search strategy was limited to English‐language publications using the following combined MeSH terms in the search strategy: (Dental Restoration OR Dental Prosthesis OR Crown OR Inlays OR Dental Abutments) and (Dental Leakage OR Prosthesis Fitting OR Dental Marginal Adaptation OR Surface Properties) and (Radiography, Dental OR Radiography, Dental, Digital OR Cone‐Beam Computed Tomography). Twenty‐eight publications were identified and read in full text, and 14 studies fulfilled criteria for inclusion. Information regarding the use of radiographic methods for the diagnosis of misfits in dental prosthesis and restorations, and in which the methodology/results comprised information regarding how the sample was collected/prepared, the method, imaging protocol, presence of a reference test and the outcomes were evaluated. QUADAS criteria was used to rate the studies in high, moderate or low quality. The evidence supporting the use of radiographic methods for the diagnosis of misfits in dental prosthesis and restorations is limited to low‐/moderate‐quality studies. The well‐established intra‐oral orthogonal projection is still under investigation and considered the most appropriate method, both when evaluating the relation between dental restoration to tooth and abutment to implant. Studies using digital radiographs have not evaluated the effect of image post‐processing, and tomography has not been evaluated.